The Impact of the Myeloid Response to Radiation Therapy - Michael J. Gough; Kristina Young; Marka Crittenden (Clinical and Developmental Immunology)
Radiation therapy is showing potential as a partner for immunotherapies in preclinical cancer models and early clinical studies. As has been discussed elsewhere, radiation provides debulking, antigen and adjuvant release, and inflammatory targeting of effector cells to the treatment site, thereby assisting multiple critical checkpoints in antitumor adaptive immunity. Adaptive immunity is terminated by inflammatory resolution, an active process which ensures that inflammatory damage is repaired and tissue function is restored. We discuss how radiation therapy similarly triggers inflammation followed by repair, the consequences to adaptive immune responses in the treatment site, and how the myeloid response to radiation may impact immunotherapies designed to improve control of residual cancer cells.